Resiko Kesehatan Pajanan PM2,5 pada Operator Stasiun Pengisian Bahan Bakar Umum (SPBU) di Kota Ternate - Sidebang, Purnama; Dianita, Nuke (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
The increase in community activity along with the increase in the number of motorized vehicles in Ternate City will affect air pollution due to the burning of motorized fuel. Motorized vehicles are the largest contributor to air pollution and the transportation sector causes 50% of the prevalence of pain in Indonesia. Gas station operators also have the risk of being exposed to pollutants such as PM2.5, PM10, CO, NO2 and other pollutants every day. These pollutants can come from motor vehicle emissions during the queue process for refueling and when leaving after refueling. It can also come from ambient air pollution around gas stations, where gas stations are usually strategically located near main roads. Exposure to high and continuous doses can have an impact on the health of gas station operators. This study aims to analyze environmental health risks due to exposure to PM2.5 in gas station operators in Ternate City. This is an observational study using the Environmental Health Risk Analysis (ARKL) method, so that a Risk Quotient (RQ) value is obtained, RQ > 1 (risky and needs to be controlled) or RQ ≤ 1 (risk does not need to be controlled). The results showed that the average respondent was female (56.2%), aged 43.6 years with a weight of 66.4 kg and had a high school/vocational education (68.8) with a smoking lifestyle (56.2%) and not consuming alcohol (81.2%). The health complaints most frequently experienced by operators were fatigue (81.2%) and headaches (56.2). The average concentration of PM2.5 at the Kalumata gas station in the morning measurements was 0.02mg/m3, afternoon and evening were 0.01mg/m3. Meanwhile at the Maliaro gas station, morning measurements were 0.06mg/m3, afternoon measurements were 0.02mg/m3 and afternoon measurements were 0.01mg/m3. Intakes of PM2.5 at gas station operators were highest in the morning measurements at Maliaro gas station, at 0.0146mg/kg/day. The results of calculating the PM2.5 Risk Level show a value of RQ>1 at the Maliaro gas station in the morning measurement. This shows the need to control exposure to PM2.5 at Maliaro gas stations, especially in the morning so that it does not cause health problems in the next 30 years.